Scattered among "the others". The Greek Presence in Bukovina in the 19th Century - Harieta Mareci Sabol; Stefan Purici (Codrul Cosminului)
Administratively organised and reorganised, 19th-century Bukovina was a full-fledged imperial limes and an outpost of the Habsburg civilisation in the so-called “Semi-Asia”, located at the crossroads of East and West and on the ethnic border between the Slavic, Finno-Ugric and Latin peoples. It was also considered a viable form of multiculturalism and ethnic, confessional, civic, and political pluralism within the Austrian paradigm, with complex, fluid, hybrid and heterogeneous identities. Some of its autochthonous population and those who had colonised or migrated there earlier, particularly their elites, proved valuable to the imperial project, due to the tolerant orientalist curiosity of the modernising agents. Although incomplete during the first part of the 19th century, statistics on the ethnic structure of the imperial province demonstrate the prominence and demographic growth of Romanians, Ruthenians, Germans, Jews, Poles, Armenians, Gypsies, and Lipovan-Russians. However, Bukovina was home to other ethnic groups, all statistically smaller and frequently included among the “others”: Italians, Slovaks, and Greeks. In the latter case, the information is dispersed throughout various documents. However, the lack of evidence, thereby hindering historical analysis, makes the presence of Greeks in Bukovina a research challenge because a community’s worth is determined not only by its size but also by the traits and roles of its members. The paper focuses on information on "marginals" in official statistics – their local communities, characteristics, and personalities in political and cultural life. The main locations of the "Greek presence", the social categories in which it is found, and the elites who assumed the Greek identity or were referred to as "Greeks from Bukovina" are both identified and discussed.